2020
DOI: 10.1016/j.gie.2020.03.3756
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation for low-grade dysplasia in Barrett’s esophagus: long-term outcome of a randomized trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 17 publications
4
30
1
3
Order By: Relevance
“…The long‐term outcomes of a randomized control trial showed that RFA in LGD significantly reduces the risk of progression after a median follow up of 73 months. 21 Our study affirms the importance in offering endoscopic therapy to the T‐LGD cohort. They are a particularly higher‐risk cohort.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The long‐term outcomes of a randomized control trial showed that RFA in LGD significantly reduces the risk of progression after a median follow up of 73 months. 21 Our study affirms the importance in offering endoscopic therapy to the T‐LGD cohort. They are a particularly higher‐risk cohort.…”
Section: Discussionsupporting
confidence: 76%
“…In our study, patients with LGD who had ablative therapy had a three times lower risk of progression relative to patients who were followed up with long‐term surveillance biopsies. The long‐term outcomes of a randomized control trial showed that RFA in LGD significantly reduces the risk of progression after a median follow up of 73 months 21 . Our study affirms the importance in offering endoscopic therapy to the T‐LGD cohort.…”
Section: Discussionsupporting
confidence: 69%
“…This concept has been further explored to develop a probe for transurethral treatment of prostate cancer allowing full or focal gland ablation under MR-guidance [247]. The imaging [154,155,189,193,214] LI: Liver [50,70,82,83,101,145,146,159,163,193,196,[215][216][217][218][219] LU: Lung [87,88,99,114,138,144,157,169,190] PA: [86,93,95,137,158,185,[193][194][195] [150][151][152][153]191] Open circles represent explorative (small/few phase I/II) use and solid black circles represent many/large phase I/II trials, retrospective analyses or phase III evidence.…”
Section: Local Heating Techniquesmentioning
confidence: 99%
“…RFA and MWA are both widely used to ablate thoracic and gastrointenstinal tumors, e.g., liver [142,145,146,263], lung [142,[147][148][149], thyroid [150][151][152][153], kidney [154,155], breast [156], esophagus [144,157] and pancreas [158]. MWA is deemed capable of creating larger and more spherical ablation zones than RFA and thus clinical results of MWA are comparable to RFA for smaller lesions, but may be better for larger lesions [145,146].…”
Section: Local Heating Techniquesmentioning
confidence: 99%
“…With confirmed LGD, the SURF study from 2014, in which 68 patients with LGD were randomized to either radiofrequency ablation (RFA) or surveillance, showed that active treatment reduced the progression to HGD or adenocarcinoma by 25% (p<0.001) [3]. Recently, a long-term follow-up study has been presented in which 96% of the patients treated with RFA experienced a sustained clearance after a median follow-up of 74 months [4]. RFA for confirmed LGD is now an integral part in most national [5] and international [6] guidelines.…”
Section: Introductionmentioning
confidence: 99%